Anti-acne activity of Casuarina equisetifolia bark extract: A randomized clinical trial (Bangladesh Journal of Pharmacology, 2014)
The objective of this study was to evaluate the clinical efficacy of Casuarina equisetifolia bark extract (5% cream) in comparison with benzoyl peroxide as the standard drug for acne vulgaris. After exclusion, fifty patients were included in the study (n=50) with age group distribution between 17-34 years of age. Patients were distributed into Group 1 (5% cream) and Group 2 (benzoyl peroxide), and were advised to apply the herbal cream twice a day topically. The clinical efficacy of the herbal cream and severity of acne vulgaris was assessed by Cook's acne grading scale. Results revealed that there was no significant difference found in both test and standard control groups. Further, remarkable improvement was found in acne grading in the test group.